RESTRUCTURING OF THE LUNG ALVEOLAR APPARATUS UNDER THE IMPACT OF THE COMPLEX OF FOOD ADDITIVES - Shevchenko, K.V.; Yeroshenko, G.A.; Donets, І.M.; Grygorenko, А.S.; Klepets, О.V.; Sokolenko, V.M.; Sharlay, N.М. (World of Medicine and Biology, 2024)
The work presents the results of a morphometric and morphological study of the respiratory department of the lungs of rats under the complex action of food additives. It was established that the use of a complex of food additives sodium glutamate, sodium nitrite and Ponceau-4R leads to changes in the morphometric parameters of the alveolar apparatus of the rats’ lungs and to violations of the structural organization of the components of the respiratory department of the lungs, which are characterized by dystrophic-destructive changes in type I and II alveolocytes, an increase the number of alveolar macrophages, accompanied by the development of interstitial and alveolar edema with the subsequent development of an allergic reaction. Restoration of morphometric indicators due to compensatory-restorative reactions does not occur.
Keywords: food additives; sodium glutamate; sodium nitrite; Ponceau-4R; pulmonary alveoli; macrophages; neutrophils; eosinophils; lungs; rats